2004
DOI: 10.1128/iai.72.9.5452-5459.2004
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of Enterohemorrhagic Escherichia coli O157 Adhering to Eukaryotic Plasma Membranes

Abstract: Using a DNA microarray, we determined changes in enterohemorrhagic Escherichia coli O157:H7 gene expression during binding to plasma membranes. Analysis of the complete transcriptomes of the bound bacteria revealed increased levels of stress-associated mRNAs and decreased levels of mRNA encoding proteins involved in translation and type III secretion.Enterohemorrhagic Escherichia coli (EHEC) is an important cause of acute gastroenteritis in humans (26). EHEC causes a wide spectrum of illnesses ranging from mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 38 publications
2
54
0
Order By: Relevance
“…This has shown that the majority of the LEE-genes were down-regulated in attached bacteria. In addition, decreased levels of two mRNAs of adjacent genes, Z3071 (Ecs2714) and Z3072 (Ecs2715), carried within prophage CP-933U, were also detected (8). Importantly, Z3072 (TccP/EspF U ) is present in EHEC but not in EPEC or C. rodentium (5,15), while Z3071 is present in EHEC, EPEC, and C. rodentium, and its product is homologous to the type III effector HopF of Pseudomonas syringae (43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has shown that the majority of the LEE-genes were down-regulated in attached bacteria. In addition, decreased levels of two mRNAs of adjacent genes, Z3071 (Ecs2714) and Z3072 (Ecs2715), carried within prophage CP-933U, were also detected (8). Importantly, Z3072 (TccP/EspF U ) is present in EHEC but not in EPEC or C. rodentium (5,15), while Z3071 is present in EHEC, EPEC, and C. rodentium, and its product is homologous to the type III effector HopF of Pseudomonas syringae (43).…”
mentioning
confidence: 99%
“…Recently, we monitored the global transcription profile of EHEC O157:H7 (Sakai strain) during attachment to eukaryotic plasma membranes (8). This has shown that the majority of the LEE-genes were down-regulated in attached bacteria.…”
mentioning
confidence: 99%
“…This novel strategy of combining signature-tagged transposon mutagenesis and microarrays could identify mutants deficient in survival in cultured macrophages and identify components of SPI 2. The results were in conformity with Baro resistant/sensitive strains Identified factors that promote barotolerance [66] Mutants and varying O 2 concentrations Gene regulation during anaerobic growth [75,98] Zinc stress Transcriptional response of E. coli to zinc [61] Attachment to eukaryotic membrane Induction of stress associated transcripts in E. coli O157:H7 and down-regulation of genes involved in TTSS [31] Intraneutrophil Induction of genes regulated by OxyR [93] Deletion of fim gene cluster Expression of surface protein antigen 43 [90] P. multocida…”
Section: Pathogenesismentioning
confidence: 61%
“…A differential expression of fim genes was observed, while deletion of the fim gene cluster led to the expression of surface protein antigen 43 [90]. Another study demonstrated differential expression of E. coli O157 genes attached to the plasma membrane of red blood cells [31]. The stress-associated mRNA increased, while levels of mRNA involved in the type III secretion system were decreased.…”
Section: Intra-macrophage Gene Expressionmentioning
confidence: 99%
“…A prerequisite for intimate attachment is elimination of EspA filaments and the NC. Indeed, we have shown that expression of the espA gene (8) and the presence of EspA filaments (35) are gradually downregulated during a 6-h infection of cells in vitro.…”
mentioning
confidence: 95%